Influence of zinc supply on the course of infectious diarrhea in children of early age - V. V. Pechuhina; O. V. Usachova (Zaporozhye State Medical University, 2024)
Aim. Give a comparative characteristic of the course of infectious diarrhea in young children, residents of the Zaporizhzhia region (Ukraine), depending on their provision of zinc (Zn). Materials and methods. The study included 99 children aged 1 to 36 months with manifestations of infectious diarrhea. On the day of hospitalization, immunochromatographic and bacteriological examination of feces was performed. Also, on the first, third and fifth days of hospitalization, a general blood test and the level of Zn in the blood were determined for each patient. Results. It was found that among the examined patients with infectious diarrhea at the onset of the disease, 22 children (22.2 %) had a reduced concentration of Zn in blood serum. In these children, the zinc level ranged from 7.63 to 9.17 μmol/l. It was also noted that the level of Zn in these patients on the 5th day of inpatient treatment rose to the norm of reference indicators. After studying the anamnesis, it was found that 40.9% of children with low Zn content had episodes of acute intestinal infection before this disease. During a comparative analysis of the clinical and laboratory data of patients, it was found that the tendency to more frequent vomiting occurred in patients with Zn deficiency (p = 0.05), that Zn availability had the most significant effect on the expressiveness of the diarrheal syndrome at the onset of the disease and more than a third (n = 8, 36.4 %) of children with Zn deficiency had more than 5 episodes of diarrhea per day, among which every second had more than 10. We did not determine significant differences between the frequency of viral and bacterial causes of diarrhea in the comparison groups. As for complete blood count, patients with Zn deficiency more often had a tendency to blood neutrophilia with a reliably frequent shift of the leukocyte formula to the left (p = 0.003). At the same time, children with a reduced content of Zn in blood serum significantly more often had lymphopenia at the onset of diarrheal disease (p = 0.006). When investigating the effect of Zn deficiency on the course of the disease, we found that in children with reduced Zn, the duration of diarrhea was almost twice as long (8 [6; 9] days vs. 5 [4; 6] in children with normal Zn indicators; p = 0.0001 according to the Mann-Whitney test) and in patients with infectious diarrhea who had Zn deficiency at the onset of the disease, on the seventh day of treatment diarrhea persisted significantly more often (p = 0.03). Such symptoms were accompanied by the persistence of signs of anemia (p = 0.06 on the 5th day) and a shift of the leukocyte formula to the left (p = 0.007) without leukocytosis. Conclusions. Almost 25 % of young children with infectious diarrhea in the Zaporizhzhia region had Zn deficiency. Most likely, Zn deficiency is caused by the peculiarities of its supply with food and its metabolism. In the debut of a diarrheal disease, insufficient supply of Zn is associated with lymphopenia and a shift of the leukocyte formula to the left. Zn deficiency in infectious diarrhea leads to a long (more than 5 days) course of the disease due to prolongation of the diarrheal syndrome.